APPLICATION OF THE SIMPLE ADDITIVE WEIGHTING (SAW) & RANK ORDER CENTROID (ROC) METHODS IN THE SELECTION OF OUTSTANDING STUDENTS AT SMK AL-HUDA SADANANYA - Husen Abdul Aziz; Adji Dwi Satria Novaldi; Cahyani Budihartanti (Journal of Information System, Informatics and Computing, 2023)
One of the obstacles to determining student achievement is that the teacher manually assesses student achievement seen from the high score of student report cards. By using this selection, it can still be felt that itl is lessl effective andl efficient andl not asl expected. Tol determine studentl achievement tol be morel accurate, ofl course, requiresl a decisionl support systeml (DSS) usingl a combinedl method, namelyl the Simplel Additive Weightingl (SAW) lmethod, which isl a weightedl addition lmethod. The basicl concept ofl the SAWl method isl to findl a weightedl sum ofl performance ratingsl for eachl alternative inl all attributesl and thel second methodl is tol use thel Rank Orderl Centroid (ROCl) method whichl is al method thatl can producel weighting ofl a numberl of criterial according tol the importancel of thel criteria lset. The authorl took 25l students dividedl from 5l students whol were rankedl in thel top 5l in eachl class ofl the 5l existing lclasses, then froml the 25l students wel processed againl with thel final resultl there werel 5 studentsl who excell with thel highest scorel namely Lilisl Napilah wasl ranked firstl with al score l0.957 followedl by Nal'il Fauzanl second withl a scorel of l0.935 thenl Dela Anandahl in thirdl place withl a scorel of l0.925 fourthl Agin Maulanal with al score ofl 0.882l and finallyl Delia Aprillizal with al score ofl 0. l860. The decisionl support systeml for selectingl outstanding studentsl at All Huda Sadananyal Vocational Schooll can bel developed intol a webl-based decisionl support systeml so thatl decision makingl can bel faster, precisel and accuratel to makel it easierl for thel school tol select outstandingl students. schoolsl to applyl for scholarships to tertiary institutions as well as for the distribution of labor.